Prognostic Values of TIM-3 Expression in Patients With Solid Tumors: A Meta-Analysis and Database Evaluation - Qin, Shuang; Dong, Bing; Yi, Ming; Chu, Qian; Wu, Kongming (Frontiers in Oncology, 2020)
Background: T cell immunoglobulin and mucin-domain containing molecule-3 (TIM-3), a novel emerging immune checkpoint molecule, was reported to express both on various kinds of immune cells and tumor cells. Many previous studies have investigated the prognostic significance of TIM-3 in cancer. However, the sample number from single study was limited and results remained controversial. Methods: We searched PubMed, Web of Science, and Embase databases for publications concerning TIM-3 expression in solid cancers up to March 2020. The correlations between TIM-3 and survival as well as clinical-pathological features were analyzed. Pooled hazard ratios (HRs), odds ratios (ORs), and 95% confidence interval (CI) were estimated by either fixed or random effects models. Results: A total of 3,072 patients were included in our meta-analysis. The result suggested that TIM-3 protein overexpression was relevant to poor overall survival (HR = 1.73, 95% CI = 1.39–2.15, P < 0.001). Moreover, TIM-3 was shown to be connected with lymph node metastasis (N+ vs. N-, OR = 1.59, 95% CI = 1.10–2.29, P = 0.013), tumor grade (G2-3 vs. G1, OR = 1.68, 95% CI = 1.21–2.34, P = 0.002), as well as PD-1 expression (PD-1high vs. PD-1low, OR = 3.26, 95% CI = 2.20–4.82, P < 0.001). In database test, significant correlations between high TIM-3 mRNA expression and poor overall survival for patients with non-small cell lung cancer and gastric cancer were observed (HR = 1.46, 95% CI = 1.23–1.72, P < 0.001; HR = 1.41, 95% CI = 1.12–1.77, P = 0.0038). Conclusion: Our meta-analysis highlights that TIM-3 has the potential to serve as a prognostic marker and a valuable therapeutic target in solid tumors.